Trans-arterial chemoembolization combined with Jinlong capsule for advanced hepatocellular carcinoma: a PRISMA-compliant meta-analysis in a Chinese population. (1st January 2020) - Jia, Shuzhao; Fu, Ying; Tao, Huimin
Abstract: Context: Jinlong capsule (JLC) is an animal-derived traditional Chinese medical preparation for advanced hepatocellular carcinoma (HCC). However, its clinical efficacy is still not well investigated. Objective: This study summarizes the efficacy and safety of JLC combined with trans-arterial chemoembolization (TACE) for patients with HCC. Methods: The databases PubMed, Cochrane Library, Web of Science, EMBASE, Medline, China National Knowledge Infrastructure, Wanfang Database, Chinese Scientific Journal Database and Chinese Biological Medicine Database were systematically searched from the date of their inception until February 2020. Jinlong capsule, trans-arterial chemoembolization, and hepatocellular carcinoma were the key terms searched. Randomized controlled trials and high-quality prospective cohort trials comparing the combined use of JLC and TACE versus TACE for HCC were included. Data were pooled using random or fixed effect models depending on heterogeneity. Results: Data from 19 articles with 1, 725 HCC patients were analysed. Compared with TACE treatment alone, the combination of TACE and JLC significantly prolonged patients' 6–36 month overall survival ( p < 0.05), and markedly improved the overall response rate (RR = 1.37, 95% CI = 1.24–1.52, p < 0.00001) and disease control rate (RR = 1.11, 95% CI = 1.06–1.17, p < 0.0001) of patients. The liver function, quality of life, and immune function of patients were significantly improved; the partial adverse events related to TACE were also effectively relieved after the combination treatment. Conclusion: This meta-analysis suggests that the combination of TACE and JLC is more effective in the treatment of HCC than treatment with TACE alone.